A novel modified culture medium for enhancing redifferentiation of chondrocytes for cartilage tissue engineering applications. (3rd February 2022) - Sonthithai, Pacharapan; Hankamonsiri, Weerawan; Lertwimol, Tareerat; Uppanan, Paweena; Janvikul, Wanida
Abstract: The dedifferentiation of articular chondrocytes during in vitro expansion deteriorates the hyaline cartilage regeneration. Many approaches have been developed to enhance the redifferentiation of chondrocytes. In this study, a new and effective protocol to improve the redifferentiation of porcine chondrocytes in a pellet form was established. Pellets were initially treated in the modified culture media containing ternary mixtures, binary mixtures, or single reagents of sodium citrate (SCi), sodium chloride (SCh), and ethylenediaminetetraacetic acid (EDTA) at varied concentrations during the first 3 days of culture, followed by a normal culture medium until 21 days. Viability, proliferation, cartilaginous gene expression, extracellular matrix formation, and morphology of treated cell pellets were comparatively examined. Chondrocytes exposed to SCi, SCh, and EDTA individually or in combinations of two or three chemicals were non‐cytotoxic when the concentration ranges of the chemicals were 1.83–2.75, 5.00–7.50, and 1.00–1.50 mM, respectively. Cells treated with the modified media containing EDTA alone and EDTA‐containing mixtures enhanced glycosaminoglycan production as well as upregulated cartilaginous gene expression, despite their low proliferation rates. Overall, when all three reagents were in use, a pronounced synergistic effect on the activations of glycosaminoglycan accumulation and type II collagen production was explicitly observed at most, particularly when cells were cultured in the medium containing SCi, SCh, and EDTA at concentrations of 2.20, 6.00, and 1.20 mM, respectively. With a use of this protocol, the redifferentiation of articular chondrocytes for regeneration of hyaline cartilage for tissue engineering applications could be readily achieved.